PENGARUH CONTENT MARKETING INSTAGRAM DAN POTONGAN HARGA TERHADAP IMPULSE BUYING - Subandrio, Subandrio; Febriani, Elsyah (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This research aims to determine Instagram content marketing and discounts on impulse buying (at the RJ Gallery store, Bengkulu City). This type of research is quantitative descriptive research. The object of this research is consumers of the RJ Gallery shop who use Instagram as a reference to see the products on offer. The sampling method is a purposive sampling technique. The number of respondents in this study was 100 respondents using the Slovin formula with 10% confidence. The data collection method uses a Google Form questionnaire with a population of ± 158,000 Instagram followers at the RJ Gallery Shop in Bengkulu City. The analysis technique uses multiple linear regression analysis tests and hypothesis testing, namely the t test and f test.                The results of this research can be concluded that partially or t test the Instagram content marketing variable (X1) has a positive and significant effect while the price discount variable (X2) partially has no effect. Simultaneously or f test the Instagram content marketing variables (X1) and price discounts (X2) on impulse buying (Y) have a positive and significant effect. The more content marketing there is on Instagram and the more discounts given according to consumer desires, the more impulse buying will increase. Keywords: Instagram Content Marketing, Price Discounts, Impulse Buying